ADAPTIVE MODEL OF ORGANIZATIONAL AND ECONOMIC SUPPORT FOR ENTERPRISES UNDER CONDITIONS OF UNCERTAINTY: THE UKRAINIAN CONTEXT - CHYZH, Vira; KAMYSHNYI, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents the development of an adaptive model of organizational and economic support for enterprises operating under conditions of multifactorial uncertainty, with a specific focus on the Ukrainian context shaped by war, economic instability, and structural disruptions. The study highlights the unprecedented challenges Ukrainian enterprises face, including infrastructure destruction, financial market volatility, logistical breakdowns, and regulatory uncertainty. Addressing these issues requires flexible management systems capable of rapid adaptation. The proposed model integrates organizational, economic, technological, and human components into a unified framework, ensuring resilience and continuity of business operations. Methodologically, it is grounded in SWOT analysis, factor analysis, and scenario planning, enabling comprehensive diagnostics of external and internal factors. The model incorporates several functional blocks: strategic planning and risk management, adaptive financial controlling and budgeting, digitalization of business processes through ERP and CRM systems, HR adaptation emphasizing flexible employment and personnel support, and marketing reorientation to digital channels and consumer behavior monitoring. By aligning theoretical foundations with international best practices (OECD, UNDP) and domestic experience, the model provides a systematic approach to overcoming crisis-induced challenges. Practical recommendations include establishing crisis-response teams, implementing adaptive budgeting, and fostering digital transformation to ensure operational sustainability. The findings demonstrate that the adaptive model not only strengthens enterprises’ resilience but also increases managerial flexibility, allowing firms to operate effectively in unstable environments. The research contributes to the theoretical development of adaptive management and offers applied tools for businesses in Ukraine to maintain competitiveness, safeguard economic security, and build long-term sustainability despite uncertainty. Prospects for further research involve industry-specific adaptation of the model and quantitative evaluation of its implementation efficiency.
Keywords: adaptive model; risk management; strategic planning; digitalization; financial controlling; HR adaptation; marketing reorientation; enterprise resilience